PENETAPAN AWAL BULAN QAMARIYAH (Antara TA’ABUDI dan TA’AQULI) - Fauzan, Fauzan (Alhurriyah, 2011)
Decision about first day of qamariyah months, especially in regard to worship (Ramadan, Shawwal, Zulhijjah) is determined by the appearance of the new moon. When the sun sets and the moon is above the horizon, which is an indication that the new moon has been there. But in reality, Ulama differ in determining whether the initial first day of qomariah months shall be based rukyat (observe of moon appearance) or can be based hisab (calculation). This is not apart from understanding dalil (reason based on Prophet exemplary).